Biofunctional response of a synthetic ceramic of 99.9% tricalcium phosphate associated with a heterologous fibrin biopolymer and infrared photobiomodulation - Reis, Carlos Henrique Bertoni; de Matos, Brenda Thaynne Lima; Bueno, Cleuber Rodrigo de Souza; Barraviera, Benedito; Ferreira Júnior, Rui Seabra; da Silva Santos, Paulo Sérgio; Duarte, Marco Antonio Hungaro; Alcalde, Murilo Priori; Nogueira, Dayane Maria Braz; Rosa Júnior, Geraldo Marco; Buchaim, Daniela Vieira; Buchaim, Rogério Leone (Frontiers in Bioengineering and Biotechnology, 2026)
Bioproducts and biomaterials for repairing large bone defects hold significant promise in translational research, particularly within Medicine and Dentistry. This study investigated a novel biocomplex comprising a synthetic tricalcium phosphate biomaterial (B), a heterologous fibrin biopolymer formulation (F), and an intraoperative photobiomodulation (PBM) protocol to enhance critical-sized bone defect repair in rats. Sixty male Wistar rats were randomly allocated to six groups (n = 10 per group): CG (blood clot control), PCG (PBM + clot), FG (fibrin), PFG (PBM + fibrin), BFG (biomaterial + fibrin), and PBFG (PBM + biomaterial + fibrin). An 8.0 mm critical-sized defect was surgically created in the parietal bone of each animal; groups PCG, PFG, and PBFG received PBM using an 808 nm infrared laser at 100 mW output power intraoperatively. Animals were euthanized at 14 and 42 days post-surgery, followed by assessments of bone repair using micro-CT, histomorphological and morphometric analyses, and immunohistochemistry. Micro-CT analyses showed progressive defect repair across all groups, with notable closure in CG (clot alone) and PFG (PBM + fibrin). Biomaterial particles in BFG and PBFG obscured radiographic visualization of new bone formation. At 14 days, significant differences emerged between CG and both PFG and PBFG (p < 0.05), with no other intergroup differences. By 42 days, CG exhibited significant differences from PFG and PBFG (p < 0.05), alongside differences between PFG and BFG, and BFG and PBFG; remaining comparisons were non-significant. Immunohistochemical markers of bone remodeling were present in all groups, indicating active repair processes. In conclusion, the combination of fibrin biopolymer and PBM proved effective in promoting bone repair and neogenesis in critical calvarial defects.